(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article summarizes current data on the causes of allergic reactions in the nail industry, focusing on the role of (meth) acrylates, cyanoacrylates, and resins. It also examines modifying risk factors, including skin barrier damage. The main clinical manifestations of allergic reactions in clients and nail technicians are presented. Particular attention is paid to diagnostics, with patch testing considered a reference method, often requiring the use of an extended (meth) acrylate allergen panel. Based on an analysis of current clinical and epidemiological data, approaches to allergic reaction prevention are systematized, including technical, professional, and medical measures aimed at minimizing allergen exposure and maintaining the skin barrier.